For a Semiotic Approach to Generative Image AI - Enzo D'Armenio; Maria Giulia Dondero; Adrien Deliège; Alessandro Sarti (Semiotic Review)
This article analyzes the semiotic functioning of Midjourney and DALL•E, two generative AI models capable of producing images out of natural language prompts. The theoretical assumption of this article is that the images produced by these AIs are the results of a particular intersemiotic translation, realized through the collaboration of human and computational operators. Our research will show the specificity of the intersemiotic translation realized by AIs vis-à-vis more classical kinds of translation (e.g., from a novel to a movie) and will also analyze the different kinds of “visual reasoning” characterizing Midjourney and DALL•E. Our article has two goals: first, to study how these models perform intersemiotic translations; namely, what choices they make in order to translate the generality of the symbolic (and indexical) signs of verbal languages into the specificity of the visual composition. Second, we intend to verify the degree of control that one can have over the visual composition. Following this, we present the results of the tests carried out on Midjourney and DALL•E pertaining to two semiotic macro-criteria: plastic categories (eidetic, chromatic, and topological) and visual enunciation (gaze relations, visual translation of verbalized actions, temporality, and aspectuality). These criteria were developed by Paris School semiotics in order to analyze artistic images. Here, they will be used as principles of composition and parameters for controlling the results. At the end, we demonstrate that through this experimentation with elementary parameters of visual composition, semiotics can provide an epistemological and analytical framework for understanding and assessing the intersemiotic translations realized through generative AIs. Reciprocally, these tests on AIs aid our understanding of the two semiotic macro-criteria used, notably leading to a multiplication of enunciative instances in image production. Databases, algorithms, prompts, and aleatoric elements act as discursive agents.